EVALUATION OF ROAD INTERSECTION ELANG - HASAN BASRI ROAD - WAY ROAD S.PARMAN- ROAD CENDRAWASIH IN SAMARINDA CITY - SETIONO, JOKO (KURVA S JURNAL MAHASISWA, 2014)
Evaluation of road intersection Elang – Hasan Basri Road – way Road Priest S.Parman Road – Cendrawasih in Samarinda City Supervisor I : Ir . Yayuk Sri Sundari , MT , and Advisor II : Rosa Agustaniah , ST , MT . Several intersections in the city of Samarinda in particular crossroads Elang – Hasan Basri Road – way Road Priest S.Parman Road – Cendrawasih , necessary to evaluate the performance of traffic lights , because the area is adjacent to the office , school and shops . So at peak hours ( peak hours ) often experience congestion and delays . The purpose of this study is to analyze the performance of traffic lights using Indonesian Highway Capacity Manual 1997 ( MKJI'97 ) at the crossroads Elang – Hasan Basri Road – way Road Priest S.Parman Road – Cendrawasih.The purpose of this study is as follows :1. Knowing the initial conditions of the performance analysis of signalized intersections at peak hours and the service level ( the level of service / LOS )2. Knowing the initial conditions of the performance analysis of signalized intersections at the average and the service level ( the level of service / LOS ) .3. Knowing the analysis of changes in traffic light timing on the performance of signalized intersections at peak hours and service levels ( the level of service / LOS ) . From the analysis of signalized intersections on roads Elang – Hasan Basri Road – way Road Priest S.Parman Road – Cendrawasih in the can ; baseline performance on peak hour intersection level of service ( the level of service / LOS ) initial conditions averaged intersection v / c = 1.208 > 0.85 have a level of service ( LOS ) = F and initial conditions intersection performance at average obtained - service levels ( the level of service / LOS ) initial conditions averaged intersection v / c = 0.913 > 0.85 have a level of service ( LOS ) = E. By the time the change made calculations on the traffic lights at the intersection of performance the level of peak hour services ( level of service / LOS ) initial conditions averaged intersection v / c = 0.741 < 0.85 have this level of service ( LOS ) = C and the change in time of traffic lights at the intersection of the performance of the average rate services ( level of service / LOS ) initial conditions averaged intersection v / c = 0.558 < 0.85 have this level of service ( LOS ) = C.